Prácticas ascéticas: un estudio de conducta y ética en la religión evangélica de la iglesia “Paz y Amor”, año 2023. - Ocampo Paño Alisson Daniela (2024)
At a global level, religion is a system of beliefs, practices and values shared by a group of people who seek to give meaning to life, providing an ethical and moral framework, which is why research has focused on understanding religion, regarding conduct and ethics and thus knowing the influence of ascetic practices, such as fasting, vigil and poverty, carried out by the members of the "Peace and Love" Missionary Church located in the Quinsaloma canton, Province of Los Ríos. This study has an analytical and field approach, since it is based on the direct and personal analysis of the experiences of a specific group of individuals. The research focused on understanding, from the perspective of those who make up this evangelical organization, how these practices influence their daily lives, their beliefs and their personal ethics since it will be known from the beginning how they approached it. The total population of the "Peace and Love" Church consists of fifty people, for this study it was decided to select a representative sample composed of five individuals, each with distinctive characteristics within the church. The method used was qualitative, using life stories as the main instrument to collect relevant information about ascetic practices and their influence on the lives of members of the Church. Keywords: Social Action, religion, ascetic practices, ethics, gospel, conduct.